Examining email etiquettes of Filipino accountancy students: Insights from Faculty members in a higher education institution - Castillo, Casey; Udtohan, Allyssa Mae; Reyno, Clyde Jeffrey; Pamplona, Angela; Nacionales, Joseph; Claridad, Norberto (Journal of Language, Literature, Social and Cultural Studies, 2023)
Effective email communication is not only a means of conveying information but also a reflection of the students’ professionalism and respect for the recipient. This study explored some best practices for accountancy students when composing emails to their faculty members, including developing a professional tone and crafting concise and meaningful emails. Qualitative approach was utilized as the framework in conducting the research and Interpretive Phenomenological Approach (IPA) was employed. Purposive-convenience sampling technique was used in gathering the participants and with the use of the thematic analysis approach, interview transcripts were read and examined many times and were organized, arranged, grouped, and coded to different themes and subthemes that reflect the purpose of the study. In presenting the findings related to the first research question, five main themes were formed (1) use of English as the definite conventional language, (2) clearly and comprehensively conveying emails using any given language, (3) the use of English language as a formal language, (4) English language as a tool in measuring competency and skills of students, (5) observing proper grammar articulation in any given language. Five concurrent themes also for the second research question (1) not giving attention to those students that do not follow email etiquette, (2) teaching and informing students the proper way of sending emails; discerning students, (3) life disposition through email, (4) presenting proper email formats that students can follow, (5) having a positive insight on the students who uses proper email etiquette.